2004
DOI: 10.2170/jjphysiol.54.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Intermittent Swimming Training on Fatty Acid Oxidation Enzyme Activity in Rat Skeletal Muscle

Abstract: Repeated exercise sessions, defined as physical exercise training, increase mitochondrial enzyme activities in skeletal muscle recruited during exercise [1][2][3][4][5][6]. Among previous studies, the types of exercise included running and cycle ergometer exercises at ϳ50-70% of maximal oxygen uptake (VO 2 max ) for more than 30 min, which is regarded as low to moderate intensity [4,[7][8][9].With respect to high-intensity exercise training, Tabata et al. [10] demonstrated that exhaustive intermittent trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 27 publications
2
28
0
4
Order By: Relevance
“…First, it has been shown that increased peroxisome proliferator activated receptor-γcoactivator-1α (PGC-1α), regarded as the master regulator of mitochondrial biogenesis in muscle, is related to the enzyme activity of 5'-AMP-activated protein kinase (AMPK), which is activated proportionally to the exercise intensity (10,52). The reason for the improvement in the aerobic capacity in HIIT can be explained by the following intracellular signaling sequence (53): muscular stimulus by HIIT increase in AMPK activity in muscle cells increase in PGC-1α mRNA and protein increase in the mRNA of the mitochondrial oxygenation enzyme increase in mitochondrial oxygenation protein improvement in physical fitness (aerobic capacity) (54). Second, it is reasonable to speculate that higher shear stress in HIIT patients during exercise bouts may trigger greater responses at the cellular and molecular levels, leading to a partial recovery from endothelial dysfunction.…”
Section: Rationale and Potential Working Mechanisms Of Hiitmentioning
confidence: 99%
“…First, it has been shown that increased peroxisome proliferator activated receptor-γcoactivator-1α (PGC-1α), regarded as the master regulator of mitochondrial biogenesis in muscle, is related to the enzyme activity of 5'-AMP-activated protein kinase (AMPK), which is activated proportionally to the exercise intensity (10,52). The reason for the improvement in the aerobic capacity in HIIT can be explained by the following intracellular signaling sequence (53): muscular stimulus by HIIT increase in AMPK activity in muscle cells increase in PGC-1α mRNA and protein increase in the mRNA of the mitochondrial oxygenation enzyme increase in mitochondrial oxygenation protein improvement in physical fitness (aerobic capacity) (54). Second, it is reasonable to speculate that higher shear stress in HIIT patients during exercise bouts may trigger greater responses at the cellular and molecular levels, leading to a partial recovery from endothelial dysfunction.…”
Section: Rationale and Potential Working Mechanisms Of Hiitmentioning
confidence: 99%
“…While adapting the Tabata protocol to swimming in rats does improve markers of oxidative capacity [4,8] whether the Tabata protocol improves mitochondrial protein content in human skeletal muscle, an adaptation that could contribute to increased aerobic capacity, is not known. The impact of the Tabata protocol on postulated regulators of skeletal muscle transcriptional (peroxisome proliferator-activated receptor γ coactivator-1 alpha [PGC-1α], sirtuin 1 [SIRT1]), and translational (mammalian target of rapamycin [mTOR] and ribosomal protein S6 kinase [S6K1]) control of mitochondrial biogenesis has also not been examined in human skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Anpassungen des Energiestoffwechsels Im Gegensatz zu der bisher weit verbreiteten Meinung, dass nur niedrigintensives umfangsorientiertes Training Anpassungen des oxidativen Stoffwechsels hervorruft, kommt es offensichtlich auch durch hochintensives Training zu Anpassungen des oxidativen Stoffwechsels [20,21]. So werden nach HIT intrazelluläre Signalwege aktiviert, die u. a. für die mitochondriale Biogenese verantwortlich sind [22].…”
Section: Ionenregulationunclassified
“…Zentrale Enzyme des oxidativen und glykolytischen Stoffwechsels (Hexokinase, Phosphofruktokinase, Citrat-Synthase, Succinat-Dehydrogenase, Malat-Dehydrogenase, Pyruvat-Dehydrogenase) sind sowohl in ihrer Dichte als auch in ihrer Aktivität nach HIT gesteigert [6,[23][24][25][26]. Des weiteren sind eine verminderte Kohlenhydratoxidation unter gleichzeitiger Erhöhung der Fettoxidation beschrieben [20,25,27,28]. Auch die muskulären Laktatkonzentrationen sind nach HIT vermindert [28].…”
Section: Ionenregulationunclassified